Destabilization of the Relationship between the Regent Authority and Dewan Perwakilan Rakyat Daerah (DPRD) in Jember, Indonesia - Nurul Azizah (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2022)
This article explores and discusses the destability of authority relations and political conflicts between regional heads and Dewan Perwakilan Rakyat Daerah (DPRD). It was this disharmony that ensued that resulted in the impeachment of the Regent. Patterns of political conflict resolution and communication dysfunction are the main issues. The issue of political conflict between the Regent and the parties in the Legislature. It became rampant in the phenomenon of regional elections directly. This research was conducted qualitatively, using the paradigm of Dahrendorf's structural-functionalism. Field data consists of narrative texts on a series of events based on personal experience. This data is in the form of transcripts of data narratives to reduce bias through comparisons between subjects and is comprehensively analyzed. The study found alignment, determinants, reconciliation archetypes, fundamental points, and prerequisites for resolution. This study concludes that there is a political conflict between regional heads and the DPRD due to the abuse of power of political parties in Parliament. Suggestions and recommendations to executive and legislative institutions should be integrated with authority relations to establish a functional structure between agencies.